2021
DOI: 10.3390/antiox10060886
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blending of Nonionic Emulsifiers Having Various Hydrophilic Head Sizes on Lipid Oxidation: Investigation of Antioxidant Polarity—Interfacial Characteristics Relationship

Abstract: The purpose of this study was to deliver insights into the effect of interfacial composition and antioxidant polarity on the lipid oxidation of emulsions. Emulsions were created using blends of nonionic ethoxylated fatty acid alcohol surfactants with different hydrophilic head sizes, and lipophilic (TBHQ) and amphiphilic (lauryl gallate) antioxidants were incorporated into the emulsions. At the same surfactant concentration, emulsion stabilized with surfactant with a smaller hydrophilic head was more susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Lee et al [ 69 ] investigated the influence of blends of surfactants on lipid oxidation, reporting that SDS prevents TBARS generation, retarding the oxidation of the emulsions. Yi et al [ 8 ] analyzed the effects of emulsifier charges on the oxidative stability of corn oil-in-water emulsions, concluding that cationic emulsions had lower oxidative stability, followed by samples with anionic and then neutral surfactants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [ 69 ] investigated the influence of blends of surfactants on lipid oxidation, reporting that SDS prevents TBARS generation, retarding the oxidation of the emulsions. Yi et al [ 8 ] analyzed the effects of emulsifier charges on the oxidative stability of corn oil-in-water emulsions, concluding that cationic emulsions had lower oxidative stability, followed by samples with anionic and then neutral surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, we employed stripped oils and deionized water (see experimental section); hence, it is not likely that such an effect can be attributed to the potential presence of prooxidant metals in the system, but the results are consistent with literature reports on the role of the interfacial charge and the nature of the surfactants employed in lipid oxidation reactions. Lee et al [69] investigated the influence of blends of surfactants on lipid oxidation, reporting that SDS prevents TBARS generation, retarding the oxidation of the emulsions. Yi et al [8] analyzed the effects of emulsifier charges on the oxidative stability of corn oil-in-water emulsions, concluding that cationic emulsions had lower oxidative stability, followed by samples with anionic and then neutral surfactants.…”
Section: Oxidative Stability Of Emulsions: Effects Of the Interfacial...mentioning
confidence: 99%
“…One of the main reasons for increased instability of oil in emulsion system compared to bulk oil is a large contact area between the oil and the water phase containing prooxidants. Moreover, previous studies showed that structural and physicochemical properties of surfactants, as well as their interactions with antioxidants in formulations, significantly influence oxidative stability of emulsified oils [ 23 , 25 , 26 , 45 , 48 ].…”
Section: Resultsmentioning
confidence: 99%